Do players communicate differently depending on the champion played? Exploring the Proteus effect in League of Legends - Şengün, Sercan; Santos, Joao M.; Salminen, Joni; Jung, Soon-gyo; Jansen, Bernard J. (Elsevier, 2022)
We investigate how the Proteus effect, which is players changing their way of communication based on characters with which they play, is associated with players’ champion usage in the popular online game League of Legends, where champions are the characters that the players control. First, we create two sets of variables: (a) objective champion characteristics based on information from the game developer, which we further enrich by semiotic coding, and (b) subjective champion characteristics based on crowdsourced opinions about the champions. Then, we analyze 13.6 million in-game chat messages to measure whether the players’ vocality (character counts of messages), valence (negative versus positive scores of language use), and toxicity (frequency of toxic word usage) change depending on the characteristics of the champions they employ. We find that champions’ body type, role, and gender are associated with players’ higher vocality, toxicity, and negative valence. We also find that the players’ communication significantly changes in toxicity and valence when they play using different champions. We discuss our methodology and results in detail and propose design directions and other implications based on them.
Keywords: Games; League of Legends; Proteus effect; Toxicity; Valence; Vocality; fi=Markkinointi|en=Marketing|